Diagnosis and Rescue of a Kinked Pulmonary Artery Catheter. (13th May 2015) - Mouawad, Nicolas J.; Stein, Erica J.; Moran, Kenneth R.; Go, Michael R.; Papadimos, Thomas J.
Abstract : Invasive hemodynamic monitoring with a pulmonary catheter has been relatively routine in cardiovascular and complex surgical operations as well as in the management of critical illnesses. However, due to multiple potential complications and its invasive nature, its use has decreased over the years and less invasive methods such as transesophageal echocardiography and hemodynamic sensors have gained widespread favor. Unlike these less invasive forms of hemodynamic monitoring, pulmonary artery catheters require an advanced understanding of cardiopulmonary physiology, anatomy, and the potential for complications in order to properly place, manage, and interpret the device. We describe a case wherein significant resistance was encountered during multiple unsuccessful attempts at removing a patient's catheter secondary to kinking and twisting of the catheter tip. These attempts to remove the catheter serve to demonstrate potential rescue options for such a situation. Ultimately, successful removal of the catheter was accomplished by simultaneous catheter retraction and sheath advancement while gently pulling both objects from the cannulation site. In addition to being skilled in catheter placement, it is imperative that providers comprehend the risks and complications of this invasive monitoring tool.